Dual‐Cargo Selectively Controlled Release Based on a pH‐Responsive Mesoporous Silica System. Issue 3 (9th December 2014) - Gui, Wanyuan; Wang, Wenqian; Jiao, Xiangyu; Chen, Lifeng; Wen, Yongqiang; Zhang, Xueji
Abstract A pH‐controlled delivery system based on mesoporous silica nanoparticles (MSNs) was constructed for dual‐cargo selective release. To achieve a better controlled‐release effect, a modified sol–gel method was employed to obtain MSNs with tunable particle and pore sizes. The systems selectively released different kinds of cargo when stimulated by different pH values. At the lower pH value (pH 2.0) only one kind of cargo was released from the MSNs, whereas at a higher pH value (pH 7.0) only the other kind of cargo was released from the MSNs. The multi‐cargo delivery system has brought the concept of selective release to new advances in the field of functional nanodevices and allows more accurate and controllable delivery of specific cargoes, which is expected to have promising applications in nanomedicine.